Transgenic maize phosphoenolpyruvate carboxylase alters leaf–atmosphere CO2 and 13CO2 exchanges in Oryza sativa - Giuliani, Rita; Karki, Shanta; Covshoff, Sarah; Lin, Hsiang-Chun; Coe, Robert A.; Koteyeva, Nuria K.; Evans, Marc A.; Quick, W. Paul; von Caemmerer, Susanne; Furbank, Robert T.; Hibberd, Julian M.; Edwards, Gerald E.; et al. (Springer, 2019)
The engineering process of C4 photosynthesis into C3 plants requires an increased activity of phosphoenolpyruvate carboxylase (PEPC) in the cytosol of leaf mesophyll cells. The literature varies on the physiological effect of transgenic maize (Zea mays) PEPC (ZmPEPC) leaf expression in Oryza sativa (rice). Therefore, to address this issue, leaf–atmosphere CO2 and 13CO2 exchanges were measured, both in the light (at atmospheric O2 partial pressure of 1.84 kPa and at different CO2 levels) and in the dark, in transgenic rice expressing ZmPEPC and wild-type (WT) plants. The in vitro PEPC activity was 25 times higher in the PEPC overexpressing (PEPC-OE) plants (~20% of maize) compared to the negligible activity in WT. In the PEPC-OE plants, the estimated fraction of carboxylation by PEPC (β) was ~6% and leaf net biochemical discrimination against 13CO2(Δbio)(Δbio) was ~ 2‰ lower than in WT. However, there were no differences in leaf net CO2 assimilation rates (A) between genotypes, while the leaf dark respiration rates (Rd) over three hours after light–dark transition were enhanced (~ 30%) and with a higher 13C composition (δ13CRd)(δ13CRd) in the PEPC-OE plants compared to WT. These data indicate that ZmPEPC in the PEPC-OE rice plants contributes to leaf carbon metabolism in both the light and in the dark. However, there are some factors, potentially posttranslational regulation and PEP availability, which reduce ZmPEPC activity in vivo